Abnormal liver function tests following inadvertent inhalation of volatile hydrocarbons. Issue 878 (December 1998) - Pyatt, J. R.; Gilmore, I.; Mullins, P. A.
Abstract : The use of aerosols containing volatile hydrocarbons in conditions of poor ventilation can result in accidental overexposure which can cause central nervous system effects and hepatic injury. We present a case in which inadvertent usage of an adhesive spray used to make greeting cards resulted in vague neurological symptoms and abnormal liver function tests both of which fully resolved on discontinuation.